Metode Regresi Data Panel untuk Meramalkan Penjualan Energi di Indonesia - Nadia Ratu Filgrima; Anneke Iswani Achmad (Bandung Conference Series: Statistics, 2022)
Abstract. Panel data is a combination of two elements, namely time-series and cross-section data. The panel data regression method aims to form a regression model that can model the effect of the independent variable on the dependent variable in several sectors observed during a certain time period of the study. Energy is one of the main needs in the survival of households and the economy in Indonesia. This study uses data on energy sold, connected power and the average electricity tariff in Indonesia in 2012-2020 which is used to analyze: Forecasting Energy Sales in Indonesia Using the Panel Data Regression Method. By using panel data and forecasting, the data used as the dependent variable (Y) is energy sold, connected power as independent variable 1 (X1) and Average Electricity Tariff as independent variable 2 (X2). In estimating the panel data regression method model, there are 3 estimates, namely: Common Effect Model, Fixed Effect Model and Random Effect Model which will later be selected as the best model, for that the results of selecting the best panel data regression model will be used to predict the dependent variable in each sector involved. observed. In this case, after the research, the best model is the Random Effect Model using the Least Square Dummy Variable (LSDV) method with the following model: Yit = 26773.16 + 1.209608X1it – 0.488954X2it – 2,551,113D1 + 11,226,73D2 – 16,173,98D3 + 7,498,361D4 – 287.8219D5 - 113.0493D6 + 12,06496D7 – 92.71225D8 + 93,255D73123,165289 93. + eit Abstrak. Data panel merupakan data gabungan antara dua unsur, yaitu data time-series dan cross-section. Metode regresi data panel bertujuan untuk membentuk suatu model regresi yang dapat memodelkan pengaruh variabel independen terhadap variabel dependen dalam beberapa sektor yang diamati selama periode waktu tertentu. Energi merupakan kebutuhan utama dalam keberlangsungan hidup rumah tangga maupun perekonomian di Indonesia. Penelitian ini menggunakan data energi terjual, daya tersambung dan tarif listrik rata-rata di Indonesia pada tahun 2012-2020 yang digunakan untuk menganalisis : Peramalan Penjualan Energi di Indonesia Menggunakan Metode Regresi Data Panel. Dengan menggunakan data panel dan peramalan, data yang digunakan sebagai variabel dependen (Y) adalah energi terjual, Daya tersambung sebagai variabel independen ke-1 (X1) dan Tarif Listrik Rata-rata sebagai variable independen ke-2 (X2). Dalam mengesitimasi model metode regresi data panel memiliki 3 estimasi yaitu : Common Effect Model, Fixed Effect Model dan Random Effect Model yang nantinya akan dipilih sebagai model terbaik, untuk itu hasil pemilihan model regresi data panel terbaik akan digunakan untuk peramalan variabel dependen pada setiap sektor yang diamati. Dalam hal ini setelah melakukan penelitian didapatkan model terbaik yaitu Random Effect Model menggunakan metode Least Square Dummy Variable (LSDV) dengan model berikut : Yit = 26773,16 + 1,209608X1it – 0,488954X2it – 2.551,113D1 + 11.226,73D2 – 16.173,98D3 + 7.498,361D4 – 287,8219D5 - 113,0493D6 + 12,06496D7 – 92,71225D8 + 93,72331D9 + 74,16528D10 + 170,3255D11 + 277,3613D12 – 134,0569D13 + eit